Narrow‐Band Red‐Emitting Phosphor K2SiF6:Mn4+: HF‐Free Synthesis, Surface Modification, and Application for Warm White LEDs. Issue 13 (4th April 2019) - Yang, Lei; Wang, Song; Wang, Yige; Wang, Jing
Abstract: Narrow‐band red‐emitting fluoride phosphors with Mn 4+ ‐doped are used as WLED backlight display source with its unique advantages. Its synthesis involving HF and its humidity‐sensitive feature hinder the application in white LED. Here, we synthesized the fluoride phosphors K2 SiF6 :Mn 4+ in a HF‐free environment and improved the chemical stability. Soaked in water for 6 h, the emission intensity of modified phosphor was measured to maintain 86% of the original state compared with that of K2 SiF6 :Mn 4+ which was kept at 72%. The as‐synthesized phosphor has an excellent color stability and thermal quenching behavior within the temperature range of 298–498 K. The white light‐emitting devices fabricated with encapsulated KSFM phosphor demonstrated the correlated color temperature (CCT) of 3334 K, color render index (CRI) of 88.91, chromaticity coordinates of (0.4176, 0.402). These considerable capabilities exhibit that this phosphor qualifies excellent performance for application in warm white LED. Abstract : We synthesized the K2 SiF6 :Mn 4+ phosphors in a HF‐free environment, of which the particle size and the emission intensity are silicon source‐dependent and improved its water resistance by surface modification with a silane. The experimental results illustrate that as‐prepared phosphor shows excellent performance for application in warm white LED.